2011
DOI: 10.3109/00365521.2011.594086
|View full text |Cite
|
Sign up to set email alerts
|

Patient and tumor characteristics may raise clinicians' awareness of familial colorectal cancer: A Norwegian population-based study

Abstract: CRC patients with right-sided colonic cancers, synchronous cancers and previous CRC and/or LS-related tumors were more likely to have familial CRC, and young age at diagnosis was not associated with familial CRC in these data. A detailed family history of colorectal cancer is essential in the identification of patients and families with familial CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…In Norwegian patients with colorectal cancers, reported by Tranø et al [10], it was found that familial colorectal cancer was associated with rightsided colonic cancers, synchronous cancers, previous colorectal cancer, and/or LS-related tumors, while age or tumor characteristics did not seem to be influencing factors. Thus, a detailed family history of colorectal cancer is essential.…”
mentioning
confidence: 91%
“…In Norwegian patients with colorectal cancers, reported by Tranø et al [10], it was found that familial colorectal cancer was associated with rightsided colonic cancers, synchronous cancers, previous colorectal cancer, and/or LS-related tumors, while age or tumor characteristics did not seem to be influencing factors. Thus, a detailed family history of colorectal cancer is essential.…”
mentioning
confidence: 91%